PENGARUH KOMPETENSI, MOTIVASI, DISIPLIN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA TAPAK TUAN. - Yani Lapian Siregar (Manajemen dan Bisnis, 2020)
Problems in this research are: How does the influence of competence on the performance of employees of the Tread Tuan Tax Service Office, how does the influence of motivation on employee performance, how does the influence of work discipline on employee performance, how does the influence of organizational commitment on employee performance, how does the influence of competence, motivation, work discipline and organizational commitment to the performance of employees of the Tread Tuan Primary Tax Service Office.The hypothesis proposed is: Competence has a positive and significant effect on the performance of the Tread Tuan Tax Office employee. Motivation has positive and significant effect on employee performance. Work discipline has positive and significant effect on employee performance. Organizational commitment has a positive and significant effect on employee performance, competence, motivation, work discipline and organizational commitment has positive and significant effect on employee performance. Sir". The research was conducted at the Pratama Tax Services Office of Jalan Tapen Tuan T.Ben Mahmud No. 26 Tapak Tuan-23718 Hilir Aceh Selatan with a research sample of 50 people. Based on the analysis results obtained Competency -t Value = 1,767, while t-table with dk 50 (Attachment) of 1,675 then t arithmetic ˃ t-table thus partially there is a significant influence between Competency on employee performance. Value of t Motivation = 3,213, while t-table with dk 50 (Attachment) is 1,675 then t arithmetic t table thus partially there is a significant influence between motivation on employee performance. The value of t work discipline = 4.040 while the t-table with dk 50 (Appendix) of 1.675 then t arithmetic t table thus partially there is a significant influence between work discipline on employee performance. The value of t organizational commitment = 4.631 while the t-table with dk 50 (Appendix) of 1.675 then t arithmetic t table thus partially there is a significant influence between organizational commitment to employee performance. The F-count value is 367,036 while the F-table value (Appendix) with the numerator dk 4 and the denominator dk 45 is 2.57 where the F-count F table (359,434 2.57) then it can be mentioned that together ( multiple) there is a positive and significant influence Competency, discipline motivation and organizational commitment, on employee performance. Thus the hypothesis 5 submitted accepted the truth.